2015
DOI: 10.1016/j.ymgme.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognition across the spectrum of mucopolysaccharidosis type I: Age, severity, and treatment

Abstract: Objectives Precise characterization of cognitive outcomes and factors that contribute to cognitive variability will enable better understanding of disease progression and treatment effects in mucopolysaccharidosis type I (MPS I). We examined the effects on cognition of phenotype, genotype, age at evaluation and first treatment, and somatic disease burden. Methods Sixty patients with severe MPS IH (Hurler syndrome treated with hematopoietic cell transplant and 29 with attenuated MPS I treated with enzyme repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
92
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 42 publications
5
92
0
1
Order By: Relevance
“…A more recent report of 22 untreated children, including the 15 previously described, found a mean IQ of 67 (well below average) at a mean age of 2.28 years. 8 Across the population, the IQ decreased with increasing age, and all died in early childhood.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A more recent report of 22 untreated children, including the 15 previously described, found a mean IQ of 67 (well below average) at a mean age of 2.28 years. 8 Across the population, the IQ decreased with increasing age, and all died in early childhood.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Past research has shown that HCT prevents progressive deterioration in cognitive outcomes into the extremely low average range among children with MPS IH, 9,10 although cognitive functioning remains below average for some children compared with same-aged peers. Regardless of statistical significance or comparisons with other groups, clinically meaningful cognitive improvement may be demonstrated with HCT treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical trials and follow-up studies of ERT in MPS I have demonstrated improvements in some somatic manifestations and functional outcomes in patients with attenuated MPS I. [8][9][10][11][12][13] Laronidase has also been found to be useful in the peritransplant period for patients with severe MPS I. 4,14 The use of ERT in the peritransplant period has been shown to be safe and has led to clinical improvements particularly in patients with significant cardiopulmonary disease before transplantation.…”
mentioning
confidence: 99%